Measuring The Legal Consistency of Special Rental Transport Licensing - Syamsuddin Baco; Nurhayati Sutan Noko'e; Sulwan Pusadan; Suarlan Datupalinge; Darwati Darwati (Publikasi Indonesia, 2023)
Special Rental Transport Arrangements, as one type of transportation of people with public motor vehicles on the road, are a response to the use of information technology as a medium of liaison between transporters and prospective passengers of public motor vehicles. But the arrangement does not place ASK complementary to other types of public transport services. The results showed that there was a different permit treatment between special rental transportation and transportation of people with public motorized vehicles not on other routes. The difference makes it easier for special rental transportation, compared to other types of transportation services. The difference is, first, the requirements for obtaining a license for a special rental transportation operator company, second, the condition that the vehicle must have proof of passing periodic tests, and third, the driver must have a General Driver's License. The norm of PM 118 of 2018 which provides the convenience (privilege) of licensing, is contrary to the norms of UULLAJ, PP Number 74 of 2014, and PM Number 117 of 2018. So that in fact, the norms of PM 118 of 2018 are void and non-binding because they conflict with legal norms that have a higher position, namely the norms of UULLAJ and PP Number 74 of 2014.